Tin-113 and Selenium-75 radiotracer adsorption and desorption kinetics in contrasting estuarine salinity and turbidity conditions. (March 2020) - Gil-Díaz, Teba; Heberling, Frank; Keller, Virginia; Fuss, Markus; Böttle, Melanie; Eiche, Elisabeth; Schäfer, Jörg
Abstract: Batch experiments were performed to study adsorption and desorption of 75 Se and 113 Sn radiotracers at environmentally representative concentrations of 0.3 ng L −1 and 3 ng L −1, respectively. The radiotracers were incubated with wet bulk sediments from the Gironde Estuary and the Rhône River, combining freshwater and coastal seawater salinity (S = 0, S = 32) and three different Suspended Particulate Matter (SPM) concentrations (10 mg L −1, 100 mg L −1, 1000 mg L −1 ) to simulate six hydrologically contrasting situations for each particle type. Results showed no measurable adsorption for 75 Se under the experimental conditions, whereas >90% of 113 Sn rapidly adsorbed onto the particles during the first hours of exposure. Adsorption efficiency increased with increasing SPM concentration and seemed to be slightly greater for the Rhône River sediments, potentially related to the intrinsic mineral composition. Desorption of spiked sediments exposed to filtered, unspiked freshwater and seawater only occurred for 113 Sn (<15% of the previously adsorbed 113 Sn) in the Garonne River sediments. This study provides insights to the potential environmental behaviour of hypothetical radionuclide releases of Se and Sn into highly dynamic and contrasting aquatic systems. Multiple accidental scenarios for the case of the Gironde Estuary and the Rhône River are discussed. These scenarios suggest that the environmental fate of soluble radionuclides like Se will be associated to water hydrodynamics and potentially more bioavailable whereas highly particle-active radionuclides like Sn will follow natural river/estuarine sedimentary regimes. Information on reactivity of radionuclides is important for improving the precision of current approaches aiming at modelling environmental radionuclide dispersion in continent-ocean transition systems. Graphical abstract: Image 1 Highlights: Nuclear waste contains Se and Sn radionuclides of safety-relevant concern. Environmentally relevant conditions are mimicked in batch experiments. Sorption of spiked 0.3 ng L −1 of 75 Se was <2%, independent of salinity. >95% of 113 Sn 3 ng L −1 was sorbed, followed by <15% desorption. Radionuclide dispersion scenarios in estuarine environments are provided.